Thermodynamic, economic, and environmental analyses of various novel ejector refrigeration subcooled transcritical CO2 systems - Yadav V.K.; Sarkar J. (My University, 2025)
The ejector refrigeration cycle has gained special interest due to its simplicity and hence can be a good choice as a subcooling device for the transcritical CO2 refrigeration system for performance improvement, which is an emerging research field. Hence, the aim of this study is the proposal and comparison of various ejector refrigeration-based dedicated subcooling methods in the CO2 refrigeration system. Six different cycle configurations (one is existing and five are novel) using the ejector refrigeration cycle for subcooling the CO2 after the gas cooler are examined. All cycles are analyzed energetically, exegetically, economically, and environmentally by developed model and compared with the reference CO2 refrigeration system (without subcooling). Effects of gas cooler pressure, generator temperature, evaporator temperature, ambient temperature, and degree of subcooling are discussed. Gas cooler pressure is optimized for maximum COP. Cycle 4 (with internal heat exchanger and gas cooler waste heat-driven generator only) yields maximum COP and exergy efficiency among all subcooling cycles at optimum operating conditions. However, the environmental pollution for cycles without an internal heat exchanger is less. In terms of cost per cooling capacity, Cycle 4 is best but having operational restriction (better for sufficiently higher temperature lift). Cycle 1 and Cycle 2 may be the better choice if heat is available. © 2021 John Wiley & Sons Ltd.